2018
DOI: 10.1108/oir-02-2017-0038
|View full text |Cite
|
Sign up to set email alerts
|

Supporting authors in documenting and sharing operative knowledge

Abstract: Purpose The purpose of this paper is to design and evaluate an authoring tool to support users in documenting knowledge using social software-based platforms in order to improve information sharing within organizations. Facilitating the creation of such content has been identified as a critical point for the acceptance of similar platforms. Design/methodology/approach The authors propose a general framework to design and assess technological solutions that positively affects users’ contribution – and, as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(24 reference statements)
0
0
0
Order By: Relevance
“…Some studies have indicated that a teaching or learning activity needs to help learners reduce the unnecessary complexity of PBL-based learning content and support the sense-making process (Marshall, 2018). Therefore, several primary characteristics of wikis can be identified as follows (Rossi & Di Iorio, 2018; W. T. Wang & Wei, 2011;Yueh et al, 2015;Zhang et al, 2019):…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Some studies have indicated that a teaching or learning activity needs to help learners reduce the unnecessary complexity of PBL-based learning content and support the sense-making process (Marshall, 2018). Therefore, several primary characteristics of wikis can be identified as follows (Rossi & Di Iorio, 2018; W. T. Wang & Wei, 2011;Yueh et al, 2015;Zhang et al, 2019):…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%